2017
DOI: 10.1002/jrs.5119
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of various phosphate minerals and occurrence of tuite in the Elga IIE iron meteorite

Abstract: The Raman spectra of phosphate minerals: apatite, merrillite, panethite, brianite, czochralskiite, maricite, new phosphate with composition of Na2Fe(Mg,Ca)(PO4)2 and high‐pressure phase tuite from the Elga IIE iron meteorite are characterized. Panethite, brianite, czochralskiite and new Na‐Fe phosphate were described for the first time. The basic features of all studied phosphates include strong ν1 symmetric stretching mode of PO43− ions at 950–990 cm−1, antisymmetric ν3 vibrations in the 1000–1175 cm−1 region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 43 publications
8
64
0
1
Order By: Relevance
“…[14,38,40] On the RS spectrum of the fluid inclusion, extra bands at 1,667-1,659 and 1,781 cm −1 are observed, due to stretching vibrations in the C¼C groups. [13,37,38] It is also highly probable that some solid inclusions, identified within the apatite crystal, host traces of low- Penel et al [29] and Borzęcka-Prokop et al [30] 1,058 ν 3 antisymmetric stretching vibrations of [PO 4 ] 3− Penel et al, [29] Frost et al, [31] and Litasov and Podgornykh [32] Penel et al [29] 962 ν 1 symmetric stretching vibrations of [PO 4 ] 3− Penel et al [29] and Litasov and Podgornykh [32] 605 CeO 2 (2TA) Schiling [33] 138 External or lattice vibrations Frost et al [31] ordered bituminous matter, indicated by the presence of a broad line in the region 1,660-1,560 cm −1 , with welldeveloped bands in the 2,950-2,850 cm −1 region [41] ( Figure 10). However, the simultaneous presence of broad features in the approximate range 1,600-1,200 cm −1 is characteristic of carbonaceous matter, and the inset in Figure 10c may indicate that inclusion has liquid content as well.…”
Section: Raman Microspectroscopymentioning
confidence: 99%
“…[14,38,40] On the RS spectrum of the fluid inclusion, extra bands at 1,667-1,659 and 1,781 cm −1 are observed, due to stretching vibrations in the C¼C groups. [13,37,38] It is also highly probable that some solid inclusions, identified within the apatite crystal, host traces of low- Penel et al [29] and Borzęcka-Prokop et al [30] 1,058 ν 3 antisymmetric stretching vibrations of [PO 4 ] 3− Penel et al, [29] Frost et al, [31] and Litasov and Podgornykh [32] Penel et al [29] 962 ν 1 symmetric stretching vibrations of [PO 4 ] 3− Penel et al [29] and Litasov and Podgornykh [32] 605 CeO 2 (2TA) Schiling [33] 138 External or lattice vibrations Frost et al [31] ordered bituminous matter, indicated by the presence of a broad line in the region 1,660-1,560 cm −1 , with welldeveloped bands in the 2,950-2,850 cm −1 region [41] ( Figure 10). However, the simultaneous presence of broad features in the approximate range 1,600-1,200 cm −1 is characteristic of carbonaceous matter, and the inset in Figure 10c may indicate that inclusion has liquid content as well.…”
Section: Raman Microspectroscopymentioning
confidence: 99%
“…Litasov and Podgornykh described the Raman spectroscopy of various phosphate minerals and the occurrence of tuite in the Elga IIE iron meteorite. This is the first finding of tuite in iron meteorites, and the only second finding of a high‐pressure mineral in them . Phan, Haeger, and Hofmeister reported the influence of the Fe 2 O 3 content on the Raman spectra of sapphires.…”
Section: Solid State Studiesmentioning
confidence: 99%
“…This is the first finding of tuite in iron meteorites, and the only second finding of a high-pressure mineral in them. [164] Phan, Haeger, and Hofmeister reported the influence of the Fe 2 O 3 content on the Raman spectra of sapphires. It was found that the Raman peaks near 418 and 578 cm -1 shift linearly with the Fe 2 O 3 content.…”
Section: Mineralsmentioning
confidence: 99%
“…A problem of sample alteration by laser beam during spectrum acquisition, especially important in the case of planetary surface investigation by rovers equipped with Raman spectrometers, was addressed in the study of Weber et al. A study of extraterrestrial phosphates in Elga meteorite, performed by Litasov and Podgornykh, allowed identifying of rare panethite, brianite, czochralskite, and a new Na 2 Fe(Mg,Ca)(PO 4 ) 2 mineral in meteoritic matter for the first time. In the paper of Stangarone et al, computational quantum chemistry was used to accurately simulate the Raman spectrum of forsterite at different temperatures in order to widen a Raman database for 2020 ExoMars mission.…”
Section: Raman Spectroscopy and Space Explorationmentioning
confidence: 99%